EMPOWERING STUDENTS OF INTERNATIONAL CLASS PROGRAMIAIN SALATIGA IN THE PRODUCTION OF PRAYING TUTORIAL VIDEO - Rifqi Aulia Erlangga; Mursid Saleh; Dwi Rukmini; Ahmad Sofwan (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
This research is to develop one method of learning that is a video containing tutorial about praying procedures in English. The video is designed to facilitate students to understand the praying procedures as well as practice their competence in English, especially listening and speaking. Some experts and the users validated the effectiveness of the research. Those who validated are people who have competence in praying procedures, English and multimedia. Therefore, there must be three experts in this research. The users are given some questionnaires asking their opinions about the video. The sample of the research was taken from college students majoring in Communication and Islam Broadcasting in IAIN Salatiga. There were 35 students in one class. Video of praying tutorial produced through this research get goodresponses from students. They feel that by watching the video and see the audio and visual movements of the prayer contained in the video can make them able to remember more clearly how to do praying, especially for praying that is not done everyday.